Crystallization and preliminary X‐ray diffraction analysis of a trimodular endo‐β‐1, 4‐glucanase (Cel5B) from Bacillus halodurans. Issue 12 (1st December 2014) - Venditto, Immacolata; Santos, Helena; Sandy, James; Sanchez‐Weatherby, Juan; Ferreira, Luis M. A.; Sakka, Kazuo; Fontes, Carlos M. G. A.; Najmudin, Shabir
<x xml:space="preserve">Abstract</x> Cellulases catalyze the hydrolysis of cellulose, the major constituent of plant biomass and the most abundant organic polymer on earth. Cellulases are modular enzymes containing catalytic domains connected, via linker sequences, to noncatalytic carbohydrate‐binding modules (CBMs). A putative modular endo‐β‐1, 4‐glucanase (BhCel5B) is encoded at locus BH0603 in the genome of Bacillus halodurans. It is composed of an N‐terminal glycoside hydrolase family 5 catalytic module (GH5) followed by an immunoglobulin‐like module and a C‐terminal family 46 CBM (BhCBM46). Here, the crystallization and preliminary X‐ray diffraction analysis of the trimodular BhCel5B are reported. The crystals of BhCel5B belonged to the orthorhombic space group P2121 2 and data were processed to a resolution of 1.64 Å. A molecular‐replacement solution has been found.